Pengaruh pembelajaran kontekstual terhadap kemampuan berpikir kritis matematis pada materi sistem persamaan linear tiga variabel - Nopyanty, Yunita; Novtiar, Chandra; Hidayat, Wahyu (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to determine the effect of contextual learning on the mathematical critical thinking skills of class X students when using the Three Variable Linear Equation System (SPLTV) material. This research method uses the experimental method. The research location is SMA Negeri 1 Cililin in the odd semester of the 2022/2023 academic year. Class X students of SMA Negeri 1 Cililin constituted the study population, while the entire study sample consisted of two randomly selected classes, an experimental class and a control class. Instruments in the form of tests of critical thinking skills have been used to collect research data. Data on the results of the mathematical critical thinking test were then analyzed using descriptive statistics and independent statistics using the Mann-Whitney test because the data did not follow a normal distribution. Based on the findings of this study, contextual learning on SPLTV material is better than conventional teaching methods.